Landscape strategy using norm structure to prevent and mitigate tsunami disaster case study in Aceh, Indonesia / Era Nopera Rauzi and Sekiguchi Nobuyuki - Rauzi, Era Nopera; Nobuyuki, Sekiguchi (2012)
Once phenomena happened in Simeulue Island where Indian tsunami occurred on December 2004 called Smong that saved villagers life. They have this knowledge because their ancestors inherited for almost a century. They remember it every day as part of their life as norm. This research purposed to use its norm structure as concept of designing landscape as prevention and mitigation planning to inform and guide people escape if tsunami appears. Landscape planning as one solution to let people learn from what is inherited by community before. It will keep both nature balance and people lives that protect and support quality of their lives for long term planning. Its concept will be differently implied according to character of the area. Comparing land types to find fits landscape strategy to improve not only environment but also quality of life then sharing the norm in community will be new concept in designing landscape plan as one of option to sustain life forwards survived tsunami. This is one way to inform and guide people to be able saving their lives if tsunami struck over again.